Performance and carcass characteristics of feedlot Nellore bulls receiving high concentrate diets with different tannin levels - Sartor Neto, Antonio; Ribeiro, Edson Luis de Azambuja; Mizubuti, Ivone Yurika; Ferreira, Elzânia Sales; Cunha, Gianne Evans; Silva, Leandro das Dores Ferreira da; Barbosa, Marco Aurélio Alves de Freitas; Bumbieris Junior, Valter Harry (Semina: Ciências Agrárias, 2011)
This study had the objective of evaluating the nutrients intake, the performance and carcass characteristics of confined bovines, submitted to high grain diets with the inclusion of different levels of tannin concentrate. Twenty-seven non castrated Nelore were used. The average age and weight at the beginning of the experiment were 18 to 20 months and 317.7 Â± 29.8 kg. Treatments had similar formulation, but varying only in the inclusion of tannin, where the control treatment had no tannin added, and the treatment 2 (0.2 TAN) had 0.2% and the treatment 3 (0.4 TAN) had 0.4% in the dry matter. Non hydrolyzed sugar cane bagasse was the only roughage used (13% of the diet dry matter). The other 87% of the diet was composed by a concentrate (corn grain, whole cottonseed, soybean meal, urea and mineral nucleus). It was used a completely randomized design. Treatments did not present statistical differences (P > 0.05) for nutrients intake, feed conversion, weight gain and carcass characteristics. Then the use of concentrated tannin up to 0.4% of the diet is not recommended.